Relationship Between Nucleos(t)ide analogue antiviral response time and prognosis in Chronic Hepatitis B: conclusions depend on baseline viral load and HBeAg status - Jingtao Huang; Xiangyong Li; Lijie You; Yutian Chong; Hong Cao (Frontiers in Pharmacology)
IntroductionCurrent guidelines for changing antiviral therapy regimens do not consider different baseline statuses. This study aimed to investigate whether significant prognostic differences exist among patients achieving virological response at various time points and whether these differences vary by viral load and HBeAg status.MethodsThis retrospective cohort study included 1,037 patients, who were classified based on their baseline viral load (high viral load, HVL, ≥ 7log10 IU mL−1: 522 individuals; or non-HVL, < 7log10 IU mL−1: 515 individuals) and HBeAg status (positive: 668 individuals; or negative: 369 individuals). Based on the virological response time, patients were grouped separately using 48 weeks and 96 weeks as the boundaries. The prognoses across these groups were evaluated and compared.ResultsPatients in the within-48-week group, 48–96-week group, and after-96-week group exhibited no significant difference in the incidence of liver disease progression (5.08% vs 4.38% vs 9.61%, p = 0.33). For HVL or HBeAg-positive patients, there was no significant difference in the cumulative incidence of liver disease progression between the within-48-week group and the 48–96-week group. In contrast, for non-HVL or HBeAg-negative patients, the cumulative incidence of liver disease progression was significantly higher in the after-48-week group than in the within-48-week group. Only the after-96-week group showed a significant increase in maintained virological response rate (p = 0.04).ConclusionAntiviral treatment should be adjusted at 48 weeks for non-HVL or HBeAg-negative patients. For HVL and HBeAg-positive patients, we suggest changing the antiviral treatment plan to 96 weeks.